Additive titanium alloy gradient laser shock fatigue life prolonging method based on structure sensitivity
By adopting the tissue-sensitive gradient laser impact method in additive titanium alloys, early tissue damage is reduced and high-level residual compressive stress is introduced, the problem of fast fatigue crack propagation rate of additive titanium alloys is solved, and the fatigue life is significantly improved.
Patent Information
- Application Number
- CN202411712602.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Additive titanium alloy components are prone to forming tiny cracks under fatigue loads, and the crack propagation rate is fast, resulting in failure of fracture. The existing laser impact strengthening methods have failed to effectively reduce the fatigue crack propagation rate.
The gradient laser impact fatigue life extension method based on tissue sensitivity is adopted to reduce tissue damage in the early stage of crack propagation, introduce a certain residual compressive stress, introduce a high level of residual compressive stress in the later stage, and set the gradient changes in laser impact process parameters to improve the expansion life of fatigue cracks.
It effectively reduces tissue damage caused by laser impact load, exerts the beneficial effect of residual compressive stress to suppress fatigue crack propagation, and significantly improves the fatigue crack propagation life of additive titanium alloys.
Smart Images

Figure CN119530523A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laser shock strengthening, and more particularly to a method for improving fatigue crack growth life by laser shock strengthening of additive titanium alloy. Background Art
[0002] At present, the use of additive manufacturing technology to achieve integrated forming of titanium alloy main bearing frames, titanium alloy integral blades and other structures has become an important development direction in the aerospace field. In actual service, additive titanium alloy components are easily damaged by foreign objects to form tiny cracks, and crack propagation under fatigue loads causes fracture failure. Therefore, how to reduce the fatigue crack propagation rate of additive titanium alloys and extend fatigue life is one of the problems that need to be solved urgently.
[0003] Laser shock peening is a non-contact, highly controllable surface modification technology that can reduce the fatigue crack growth rate by inducing a work hardening layer and a residual compressive stress layer on the surface of the material. However, after laser shock treatment, the fatigue crack growth rate of the additive titanium alloy increases instead of decreases. The reasons are as follows: (1) In additive titanium alloys, fatigue cracks tend to propagate along the basal and cylindrical surfaces of the α phase; (2) Under laser shock load, the α phase produces slip steps along the basal and cylindrical surfaces, forming tissue damage and accelerating crack growth.
[0004] Therefore, it is particularly important to reduce tissue damage caused by laser shock loads, give full play to the beneficial effects of residual compressive stress, and propose an implementation method for laser shock strengthening suitable for additive titanium alloys. Summary of the invention
[0005] In view of this, the present invention provides an additive titanium alloy gradient laser shock fatigue life extension method based on tissue sensitivity, which achieves the goal of introducing a certain level of residual compressive stress in the early stage of crack propagation while reducing tissue damage, and introducing a high level of residual compressive stress in the late stage of crack propagation, thereby increasing the propagation life of fatigue cracks.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The method of extending the fatigue life of additive titanium alloy gradient laser shock based on tissue sensitivity includes:
[0008] Determine the microstructure sensitivity transition point of the standard compact tensile specimen, and calculate the critical crack length corresponding to the microstructure sensitivity transition point;
[0009] Setting the same strengthening area on both sides of the standard compact tensile specimen, and marking the end position of the critical crack length as the critical point;
[0010] In the strengthening area, n strengthening belts are arranged in sequence;
[0011] Setting laser shock process parameters for each strengthening zone, wherein the laser shock process parameters before the critical point are smaller than the laser shock process parameters after the critical point;
[0012] placing a strengthening area on one side of the standard compact tensile specimen within a laser shock processing range, and performing laser shock processing according to laser shock process parameters corresponding to the strengthening zone;
[0013] Then, the strengthening area on the other side of the standard compact tensile specimen is placed within the laser shock processing range, and laser shock processing is performed according to corresponding laser shock process parameters.
[0014] Furthermore, the determining of the tissue sensitivity transition point of the standard compact tensile specimen and the calculation of the critical crack length corresponding to the tissue sensitivity transition point specifically include:
[0015] Perform fatigue crack growth test on standard compact tensile specimen, draw relationship curve between crack growth rate and stress intensity factor range, and obtain the microstructure sensitivity transition point of the standard compact tensile specimen;
[0016] The critical crack length corresponding to the tissue sensitivity transition point is solved by using the stress intensity factor range calculation formula.
[0017] Furthermore, the strengthening area is 1 mm away from the root of the notch of the standard compact tensile specimen.
[0018] Furthermore, in the strengthening area, n strengthening belts are sequentially arranged, including:
[0019] In the strengthening area, the light spot is moved in a direction perpendicular to the cut of the standard compact tensile specimen to form a first strengthening band;
[0020] The light spot is shifted in a direction parallel to the notch of the standard compact tensile specimen, and the movement continues to form a second strengthening band;
[0021] Until the entire strengthening area is covered, a total of n strengthening belts are formed.
[0022] Furthermore, the light spot is a circular light spot with a diameter of 3 mm, a laser wavelength of 1064 nm, and a pulse width of 15 ns.
[0023] Furthermore, the overlap rate of the light spot is 50%, and the overlap rate of the reinforcement belt is 50%.
[0024] Furthermore, the laser shock process parameters include laser shock energy and the number of laser shocks; the laser shock energy varies in the range of 1J to 10J, and the number of laser shocks varies in the range of 1 to 3 times.
[0025] Furthermore, the laser shock treatment specifically includes:
[0026] An absorption layer and a constraint layer are added to the surface of the standard compact tensile specimen, and a nanosecond pulse laser is focused on the surface of the standard compact tensile specimen to complete the laser shock treatment of the strengthened area.
[0027] Furthermore, the absorption layer is an aluminum foil with a thickness of 100 μm, and the constraint layer is a water film with a thickness of 1 mm.
[0028] It can be seen from the above technical scheme that compared with the prior art, the present invention discloses a method for extending the fatigue life of additive titanium alloy by gradient laser shock based on tissue sensitivity, which fully considers the differences in tissue sensitivity of additive titanium alloy at different crack propagation stages, and sets the laser shock process parameters in a gradient change form from small to large, using a smaller laser shock energy before the critical point and a larger laser shock energy after the critical point; the adverse effects of laser shock tissue damage on crack propagation are avoided, the beneficial effect of residual compressive stress in inhibiting fatigue crack propagation is brought into play, and the fatigue crack propagation life of additive titanium alloy is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 A schematic diagram of the laser shock strengthening method for CT samples with gradient changes in laser shock process parameters provided by the present invention.
[0031] Figure 2 This is the CT sample size used in the embodiment of the present invention.
[0032] Figure 3 Graph showing the relationship between crack growth rate and stress intensity factor range in an embodiment of the present invention.
[0033] Figure 4 This is a diagram of the laser shock peening area setting in an embodiment of the present invention.
[0034] Figure 5 A schematic diagram of a conventional laser shock strengthening method for CT samples with constant laser shock process parameters provided by an embodiment of the present invention;
[0035] Figure 6 A surface residual stress distribution curve provided by an embodiment of the present invention;
[0036] Figure 7 A relationship curve between fatigue crack extension length and cycle number provided in an embodiment of the present invention;
[0037] Figure 8 A schematic diagram of a laser shock strengthening method for an additive titanium alloy plate with edge cracks provided by an embodiment of the present invention;
[0038] Description of the drawings: 1 is a CT sample cut, A1 is a positive strengthening area, and A2 is a negative strengthening area. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Before introducing this embodiment, the standard compact tensile specimen used in this embodiment is first introduced. The standard compact tensile specimen, referred to as CT specimen, is a specimen specially used to evaluate the fracture toughness of a material. A cyclic fatigue load can be applied to determine the crack propagation behavior of the material.
[0041] The embodiment of the present invention discloses a method for extending the fatigue life of an additive titanium alloy by gradient laser shock based on tissue sensitivity, referring to Figure 1 As shown, including:
[0042] Determine the microstructure sensitivity transition point of the standard compact tensile specimen, and calculate the critical crack length corresponding to the microstructure sensitivity transition point;
[0043] Setting the same strengthening area on both sides of the standard compact tensile specimen, and marking the end position of the critical crack length as the critical point;
[0044] In the strengthening area, n strengthening belts are arranged in sequence;
[0045] Setting laser shock process parameters for each strengthening zone, wherein the laser shock process parameters before the critical point are smaller than the laser shock process parameters after the critical point;
[0046] placing a strengthening area on one side of the standard compact tensile specimen within a laser shock processing range, and performing laser shock processing according to laser shock process parameters corresponding to the strengthening zone;
[0047] Then, the strengthening area on the other side of the standard compact tensile specimen is placed within the laser shock processing range, and laser shock processing is performed according to corresponding laser shock process parameters.
[0048] Based on the characteristics that fatigue crack propagation of additive titanium alloy has strong tissue sensitivity in the early stage and weak tissue sensitivity in the later stage, the present invention proposes a laser shock strengthening method with gradient change of laser shock process parameters, so as to achieve the goal of introducing a certain residual compressive stress under the premise of reducing tissue damage in the early stage of crack propagation, and introducing a high level of residual compressive stress in the later stage of crack propagation, thereby improving the propagation life of fatigue cracks.
[0049] The following are the specific steps of this method:
[0050] Step 1: Determine the microstructure sensitivity transition point of the standard compact tensile specimen and calculate the critical crack length corresponding to the microstructure sensitivity transition point;
[0051] According to GB / T 6398-2017 "Metallic Materials Fatigue Crack Growth Rate Test Method", fatigue crack growth test of standard compact tensile specimens was carried out, and the relationship curve between crack growth rate (da / dN) and stress intensity factor range (ΔK) was plotted to obtain the microstructure sensitivity transition point ΔK of additive TC4 titanium alloy. t .
[0052] Using the calculation formula of stress intensity factor range ΔK, solve the tissue sensitivity transition point ΔK t The corresponding critical crack length a t The calculation formula of stress intensity factor range ΔK is as follows:
[0053]
[0054] Where ΔP = P max (1-r) is the applied fatigue load range, B is the thickness of the CT specimen, W is the width of the CT specimen, a is the crack length, P max is the maximum value of the applied fatigue load and r is the stress ratio.
[0055] Step 2: Strengthen regional settings;
[0056] The same strengthening area is set on the front and back sides of the standard compact tensile specimen, and the strengthening area is 1mm away from the root of the notch of the standard compact tensile specimen; and the specific position of the critical crack length is marked in the strengthening area, which is used as the critical point;
[0057] Step 3: Strengthen the belt setting;
[0058] In the strengthening area, the light path is fixed and the workpiece is moved, so that the light spot moves in a direction perpendicular to the notch of the standard compact tensile specimen to form the first strengthening band; then, the light spot is offset in a direction parallel to the notch of the standard compact tensile specimen and continues to move to form the second strengthening band; until the entire strengthening area is covered, a total of n strengthening bands are formed, where n is a positive integer greater than 1.
[0059] The spot is the smallest diameter area after the laser beam is focused, usually a circular area with high energy density.
[0060] In this embodiment, the circular spot diameter is 3 mm, the laser wavelength is 1064 nm, and the pulse width is 15 ns; precise control of the strengthening area of the standard compact tensile specimen can be achieved, thereby improving the surface properties and fatigue resistance of the material.
[0061] The overlap rate of the light spot refers to the ratio of the overlap between adjacent light spots to the diameter of a single light spot. A 50% overlap rate means that if the diameter of the light spot is D, the spacing between adjacent light spots is 0.5D.
[0062] In this embodiment, the overlap rate of the light spots is 50%, and the overlap rate of the strengthening belts is 50%, which means that there is a certain overlap between each strengthening belt and each light spot to ensure the uniformity and continuity of the entire strengthening area.
[0063] Step 4: Setting the laser shock process parameters for each strengthening belt;
[0064] The strengthening zone located before the critical point is treated with small laser shock process parameters to avoid tissue damage; the strengthening zone located after the critical point is treated with large laser shock process parameters to introduce a high level of residual compressive stress.
[0065] In this embodiment, the 1st to nth strengthening bands are set with gradually enhanced laser shock process parameters, including laser shock energy and number of laser shocks; wherein the laser shock energy varies in the range of 1J to 10J, and the number of laser shocks varies in the range of 1 to 3 times.
[0066] The gradually increasing laser impact energy and number can gradually increase the residual compressive stress on the material surface, and better exert the beneficial effect of residual compressive stress in inhibiting fatigue crack propagation while avoiding tissue damage.
[0067] Step 5: Laser shock strengthening of the front side of the standard compact tensile specimen;
[0068] The workpiece motion system is controlled so that the front strengthening area of the standard compact tensile specimen is within the processing range. After adding the absorption layer and the constraint layer, the nanosecond pulse laser is focused on the surface of the standard compact tensile specimen. According to the strengthening band setting of step three and the process parameter setting of step four, the laser shock treatment of the front strengthening area is completed.
[0069] In which, an absorption layer is coated on the front reinforcement area of the standard compact tensile specimen, usually using black paint or metal film to improve the absorption efficiency of laser energy. In this embodiment, the absorption layer is a 100μm thick aluminum foil. A constraint layer is covered on the absorption layer, usually using glass or polyurethane material to prevent the high-pressure gas generated during the laser impact from escaping. In this embodiment, the constraint layer is a 1mm thick water film.
[0070] After adding the absorption layer and the constraint layer, the positive reinforcement area of the standard compact tensile specimen is precisely laser-shocked using a nanosecond pulse laser, and the laser shock energy and number are gradually increased to achieve finer control of material properties.
[0071] Step 6: Laser shock strengthening of the reverse side of the standard compact tensile specimen;
[0072] Control the workpiece motion system so that the reverse side strengthening area is within the processing range, and refer to step 5 to complete the reverse side laser shock treatment.
[0073] The embodiment of the present invention measures the tissue sensitivity transition point ΔK from the perspective that the tissue sensitivity is strong in the early stage of crack propagation of the additive titanium alloy and weak in the later stage. t The corresponding critical crack length a is calculated t , a laser shock strengthening method with step-by-step increase in laser shock energy and number of times was proposed, achieving mutual matching between microstructure, residual compressive stress and different crack lengths.
[0074] The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity proposed in the present invention is specifically described in the following embodiments.
[0075] Embodiment 1
[0076] First, the CT sample used in this example is referenced Figure 2 shown.
[0077] Afterwards, the laser shock peening method provided by the present invention is operated.
[0078] According to step 1, first determine the tissue sensitivity transition point, and then calculate the corresponding critical crack length;
[0079] Firstly, according to GB / T 6398-2017 “Test Method for Fatigue Crack Growth Rate of Metallic Materials”, the fatigue crack growth test of CT specimens was carried out, and the relationship curve between crack growth rate (da / dN) and stress intensity factor range (ΔK) was plotted to obtain the microstructure sensitivity transition point ΔK of additive TC4 titanium alloy. t .
[0080] The cyclic fatigue load P used in this embodiment max=1000N, stress ratio r=0.1. Figure 3 As shown in the figure, the relationship curve between the crack growth rate (da / dN) and the stress intensity factor range (ΔK) of the additive TC4 titanium alloy exists. There are two crack growth stages with different slopes, and the intersection point is the microstructure sensitivity transition point ΔK t =13.5MPa·m 1 / 2 .
[0081] Secondly, the stress intensity factor range ΔK calculation formula is used to solve the tissue sensitivity transition point ΔK t The corresponding critical crack length a t .
[0082] The calculation formula of stress intensity factor range ΔK is as follows:
[0083]
[0084] In this embodiment, ΔP = 900N, B = 5mm, W = 25mm, and ΔK is obtained by solving t The corresponding a t =12.4mm.
[0085] Follow step 2 to set the enhanced area, refer to Figure 4 As shown in the figure, a 18mm×15mm strengthening area is set on the front and back sides of the CT specimen. The strengthening area is 1mm away from the root of the CT specimen cut 1, and the positions of the front and back strengthening areas are aligned. The front strengthening area is A1 and the back strengthening area is A2. The critical crack length a corresponding to the tissue sensitivity transition point is marked in the strengthening areas A1 and A2. t =Specific location of 12.4mm.
[0086] According to step 3, the strengthening belt is set. In the strengthening areas A1 and A2, the optical path is fixed and the workpiece is driven by the robot arm to move, so that the light spot moves in a direction perpendicular to the CT sample cut 1 to form the first strengthening belt; then, the light spot is offset in a direction parallel to the CT sample cut and continues to move to form the second strengthening belt; until the entire strengthening area is covered, a total of 9 strengthening belts are formed, which are named strengthening belts L1 to L9 respectively.
[0087] Since the diameter of the light spot is 3 mm, in the same enhanced band, the center distance between adjacent light spots is 1.5 mm, and the light spot offset between adjacent enhanced bands is 1.5 mm.
[0088] According to step 4, the laser shock process parameters of each strengthening belt are set. The laser shock energy of the strengthening belts L1 to L9 is set to 1J to 9J respectively, and the number of laser shocks is 2 times.
[0089] The reinforcement zone located before the critical crack length corresponding to the tissue sensitivity transition point is treated with small laser shock process parameters to avoid microscopic tissue damage; the reinforcement zone located after the critical crack length corresponding to the tissue sensitivity transition point is treated with large laser shock process parameters to introduce a high level of residual compressive stress.
[0090] In this embodiment, the reinforcement strips L1 to L3 are located at a t =12.4mm, the laser shock energy is set to 1J to 3J, and the strengthening belts L4 to L9 are located at a t =12.4mm, the laser impact energy was set to 4J to 9J respectively.
[0091] The laser shock energy of the reinforcing bands L1 to L3 can also be set to 1J, and the laser shock energy of the reinforcing bands L4 to L9 can be set to 4J to 9J respectively; no specific limitation is made here, as long as the laser shock energy of the reinforcing bands L1 to L3 is less than the laser shock energy of the reinforcing bands L4 to L9.
[0092] According to step five, the front side of the CT sample is laser-shock-hardened. The robot arm is controlled to place the front strengthening area A1 of the CT sample within the laser-shock processing range. A 100 μm thick aluminum foil is pasted on the surface of the front strengthening area A1 as an absorption layer, and a 1 mm thick water film is covered as a constraint layer.
[0093] Subsequently, the robot arm is controlled to move along the path of the strengthening belts L1 to L9 in step 3, and the laser impact energy of the strengthening belts L1 to L9 is set to 1J to 9J to complete the first impact of the front strengthening area A1.
[0094] After replacing the new aluminum foil and covering it with a water film, the second impact of the front reinforcement area A1 was completed.
[0095] According to step six, the back side of the CT sample is laser-shock-processed, and the robot arm is controlled to place the back side strengthening area A2 of the CT sample within the laser-shock processing range. Step five is repeated to complete the laser-shock processing of the back side strengthening area A2.
[0096] Example 1 is a laser shock peening test of a CT sample with a gradient change in laser shock process parameters, and the CT sample obtained after laser shock peening is referred to as CT sample 1.
[0097] Embodiment 2
[0098] Example 2 is used as a control experiment, referring to Figure 5As shown, in Example 2, a conventional laser shock strengthening test of a CT sample with constant laser shock process parameters is carried out. In step 4, the laser shock energy of the strengthening bands L1 to L9 is set to 8J, the number of laser shocks is set to 2, and the other steps are exactly the same as in Example 1. Finally, a laser-treated CT sample is obtained, which is called CT sample 2.
[0099] After that, residual stress test is carried out, using X-ray diffractometer or stress meter to measure the residual stress distribution on the material surface; fatigue test is carried out to measure the fatigue life of the material under different laser shock parameters. The effect of laser shock treatment is evaluated to ensure the optimization of process parameters and the improvement of material performance.
[0100] In the residual stress test, the X-ray diffractometer uses the principle of X-ray diffraction to analyze the crystal structure of the material and calculate the residual stress inside the material.
[0101] Test results reference Figure 6 As shown, it is the distribution curve of the measured surface residual stress at different distances from the root of the incision 1.
[0102] CT sample 1 was obtained by implementing the method of process parameter gradient change, which introduced increasing residual compressive stress on the surface of the CT sample, gradually increasing from 50MPa to 550MPa. CT sample 2 was obtained by implementing the method of process parameter gradient constant, which introduced a relatively consistent residual compressive stress of about 450MPa on the surface of the CT sample.
[0103] In this embodiment, the fatigue test uses a fatigue testing machine, which can apply cyclic loads to simulate the fatigue behavior of materials under actual working conditions. The fatigue load used is 1000N and the stress ratio is 0.1. Figure 7 The figure shows the relationship between fatigue crack extension length and cycle number. It is concluded that the fatigue life of CT sample 2 is lower than that of the untreated sample. In the early stage of crack extension, due to the presence of tissue damage, it shows a faster crack extension rate (the slope of the curve represents the crack extension rate); the fatigue crack extension life of CT sample 1 is increased by more than 30%.
[0104] Embodiment 3
[0105] This embodiment applies the additive titanium alloy gradient laser shock fatigue life extension method based on tissue sensitivity to additive titanium alloy plates with edge cracks. Figure 8 As shown, a laser shock method for additive titanium alloy plates containing edge cracks was developed based on the CT specimen.
[0106] First, a standard CT specimen with the same thickness as the additive titanium alloy plate was prepared;
[0107] Secondly, based on the fatigue load ΔP borne by the additive titanium alloy plate, the fatigue crack growth test of the standard CT specimen was performed to measure the tissue sensitivity transition point ΔK t And calculate the critical crack length a t ;
[0108] Then, compare the edge crack length a with the critical crack length a t The relationship between the edge crack and the tissue sensitivity transition point can be determined.
[0109] Finally, a laser shock treatment plan is formulated according to steps 2 to 6 in the first embodiment.
[0110] Furthermore, the tissue sensitivity transition point ΔK t It is the intrinsic property of the additive titanium alloy and does not change due to the fatigue load ΔP or the sample size; however, the tissue sensitivity transition point ΔK t The calculated critical crack length a t Affected by the external load ΔP and the sample size, it is necessary to ensure that the thickness of the prepared standard CT sample is consistent with the additive titanium alloy plate.
[0111] The method for extending the fatigue life of additive titanium alloy by gradient laser shock treatment based on tissue sensitivity proposed in the present invention fully considers the characteristics of additive titanium alloy fatigue crack extension with strong tissue sensitivity in the early stage and weak tissue sensitivity in the later stage. Specifically, in the early crack extension area, laser shock treatment is performed using smaller process parameters to introduce certain residual compressive stress while reducing tissue damage; in the later crack extension area, due to the weakening of tissue sensitivity, the laser shock process parameters can be increased to introduce high residual compressive stress.
[0112] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the method disclosed in Example 3, since it corresponds to the method disclosed in Example 1, the description is relatively simple, and the relevant parts can be referred to the method part description.
[0113] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for extending the fatigue life of additive titanium alloys by gradient laser shock based on tissue sensitivity, characterized in that: include: Determine the microstructure sensitivity transition point of the standard compact tensile specimen, and calculate the critical crack length corresponding to the microstructure sensitivity transition point; Setting the same strengthening area on both sides of the standard compact tensile specimen, and marking the end position of the critical crack length as the critical point; In the strengthening area, n strengthening belts are arranged in sequence; Setting laser shock process parameters for each strengthening zone, wherein the laser shock process parameters before the critical point are smaller than the laser shock process parameters after the critical point; placing a strengthening area on one side of the standard compact tensile specimen within a laser shock processing range, and performing laser shock processing according to laser shock process parameters corresponding to the strengthening zone; Then, the strengthening area on the other side of the standard compact tensile specimen is placed within the laser shock processing range, and laser shock processing is performed according to corresponding laser shock process parameters.
2. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 1, characterized in that: The step of determining the tissue sensitivity transition point of the standard compact tensile specimen and calculating the critical crack length corresponding to the tissue sensitivity transition point specifically includes: Perform fatigue crack growth test on standard compact tensile specimen, draw relationship curve between crack growth rate and stress intensity factor range, and obtain the microstructure sensitivity transition point of the standard compact tensile specimen; The critical crack length corresponding to the tissue sensitivity transition point is solved by using the stress intensity factor range calculation formula.
3. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 1, characterized in that: The distance between the strengthened area and the notch root of the standard compact tensile specimen is 1 mm.
4. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 1, characterized in that: In the strengthening area, n strengthening belts are arranged in sequence, including: In the strengthening area, the light spot is moved in a direction perpendicular to the cut of the standard compact tensile specimen to form a first strengthening band; The light spot is shifted in a direction parallel to the notch of the standard compact tensile specimen, and the movement continues to form a second strengthening band; Until the entire strengthening area is covered, a total of n strengthening belts are formed.
5. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 4, characterized in that: The light spot is a circular light spot with a diameter of 3 mm, a laser wavelength of 1064 nm, and a pulse width of 15 ns.
6. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 4, characterized in that: The overlap rate of the light spot is 50%, and the overlap rate of the reinforcement belt is 50%.
7. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 1, characterized in that: The laser shock process parameters include laser shock energy and laser shock times; the laser shock energy varies in the range of 1J to 10J, and the laser shock times varies in the range of 1 to 3 times.
8. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 1, characterized in that: The laser shock treatment specifically includes: An absorption layer and a constraint layer are added to the surface of the standard compact tensile specimen, and a nanosecond pulse laser is focused on the surface of the standard compact tensile specimen to complete the laser shock treatment of the strengthened area.
9. The method for extending the life of additive titanium alloy gradient laser shock fatigue based on tissue sensitivity according to claim 8, characterized in that: The absorption layer is an aluminum foil with a thickness of 100 μm, and the constraint layer is a water film with a thickness of 1 mm.